Film review as an approach in teaching and learning fundamental of Islam / Farah Safura Muhammud - Muhammud, Farah Safura (2021)
21st century learning requires lecturers to change from traditional learning to student-focused learning as well as applying critical learning and critical thinking skills. The film approach has been used in the subject Fundamental of Islam (CTU101) which is a compulsory subject for year 1 students of UiTM. This study is to identify the effectiveness of the film approach and the ability of students to integrate understanding related to Fundamental of Islam in film contents. The problem statement states two issues; firstly, learning challenges during the COVID-19 pandemic period and secondly learning challenges for Islamic Studies subjects. This study has selected five films that are included in the CTU101 syllabus, namely, My Name Is Khan, 2012, Laskar Pelangi, Jilbab Traveler, and Joker. This research used quantitative data to hundred CTU101 students and analysed using SPSS 20.0 software. This research has shown all positive reactions and happiness from students. Learning through films, well guided from a lecturer will then be a good approach for Islamic Studies subjects. The findings of the study show that students feel fun and easy to apply the fundamentals of Islam in daily life. Hence, watching movies while studying can alleviate some of the stress in the pandemic season that demands learning online.